Cichorium intybus: Traditional Uses, Phytochemistry, Pharmacology, and Toxicology. (26th November 2013) - Street, Renée A.; Sidana, Jasmeen; Prinsloo, Gerhard
Abstract : The genus Cichorium (Asteraceae) is made up of six species with major geographical presence in Europe and Asia. Cichorium intybus, commonly known as chicory, is well known as a coffee substitute but is also widely used medicinally to treat various ailments ranging from wounds to diabetes. Although this plant has a rich history of use in folklore, many of its constituents have not been explored for their pharmacological potential. Toxicological data on C. intybus is currently limited. This review focuses on the economic and culturally important medicinal uses of C. intybus . Traditional uses, scientific validation, and phytochemical composition are discussed in detail.